Tinjauan Tingkat Kebugaran Jasmani Siswa Kelas VIII Sekolah Menengah Pertama Negeri 1 Sijunjung: indonesia - Dwi Natalia Parwati; Yaslindo; Mario Febrian; Sefri Hardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was that the level of physical fitness of eighth-grade students at State Junior High School 1 Sijunjung had not yet been identified. This study aimed to determine the physical fitness level of eighth-grade students at State Junior High School 1 Sijunjung. This research employed a quantitative descriptive method. The population consisted of all eighth-grade students at State Junior High School 1 Sijunjung, totaling 155 students, comprising 66 male students and 89 female students. The sample was selected using proportionate stratified random sampling, resulting in 31 students, consisting of 9 male students and 22 female students. Data were collected using the Indonesian Student Fitness Test (Tes Kebugaran Siswa Indonesia/TKSI) Phase D for junior high school students, which included Hand-Eye Coordination, Sit-Up, Standing Broad Jump, T-Test, and Multi-Stage Fitness Test. The data were analyzed using quantitative descriptive statistics. The results showed that the average physical fitness score of the eighth-grade students at State Junior High School 1 Sijunjung was 15.19. These findings